Inflammasome activation in ruminant cells infected with Chlamydia abortus - Doull, Laura Elizabeth (The University of Edinburgh, 2016)
Chlamydia abortus is the most common known infectious cause of ovine abortion worldwide but is rarely linked with bovine abortion. The reasons for this differential pathogenesis are unknown but may involve differences in innate immune recognition and immune responsiveness. This is supported by the observation that chlamydial abortion in sheep is associated with an inflammatory cytokine/chemokine cascade that is not commonly observed in cattle. Studies with other Chlamydia species have demonstrated that innate inflammatory pathways including inflammasome activation contribute to both pathogen clearance and pathology. Pattern recognition receptors (PRRs) activate these innate immune signalling pathways but are relatively poorly characterized in ruminants. We hypothesize that the ruminant hosts differ in their ability to innately sense C. abortus infection and activate the inflammasome. The main aims of this project were to: analyse PRR expression in innate immune cells; assess cytokine production from innate immune cells in response to C. abortus; investigate the role of PRRs in the induction of innate immune responses to C. abortus; and, conduct RNA-seq analysis on macrophages following infection with C. abortus to identify important immune signalling pathways. Ruminant oro-nasal turbinate cells, monocyte derived dendritic cells (MDDCs) and monocyte derived macrophages (MDMs) express the cell-surface PRRs TLR2 and TLR4 and also the intracellular PRRs NOD 1 and NLRP3. Oro-nasal turbinate cells produce CXCL8 late into the chlamydial developmental cycle independent of IL-1β. In contrast, ruminant MDMs and MDDCs secrete early IL-1β in response to C. abortus infection. In MDMs and MDDCs, live and UV-inactivated C. abortus induced TNF-α and CXCL8 but live infection was required for IL-1β secretion. Therefore, intracellular C. abortus multiplication is necessary to stimulate the IL-1β processing pathway within these cells. In order to determine PRR function, NOD1 and NLRP3 were knocked down in ruminant MDMs using siRNA. In both ovine and bovine MDMs, NOD1 was identified as a factor in C. abortus mediated IL-1β production. NLRP3 knockdown in bovine but not ovine MDMs also reduced IL-1β production, indicating species-specific differences in C. abortus recognition. The RNA-seq analysis of ruminant MDMs identified novel pathways of immune activation by C. abortus and potentially important species-specific differences. An improved understanding of the innate immune pathways activated in susceptible and resistant hosts following C. abortus infection will inform on disease pathogenesis and could contribute to novel chlamydial vaccine design.
Keywords: Chlamydia abortus; inflammasome; cytokine; pathogen recognition; pattern recognition receptor; PRR